South East Resource Region Development Plan - Union Economic Development Including Demographic Aspects (Union Economic Development Including Demographic Aspects, 1970)
The South East Resource Region (S.E.R.R), covering parts of West Bengal, Bihar, Orissa, Madhya Pradesh, and Uttar Pradesh, has experienced significant economic growth between 1955 and 1965, with total income more than doubling from Rs. 611 crores to Rs. 1,292 crores. Industrial and manufacturing sectors, particularly in coal and steel-rich districts such as Dhanbad and Singhbhum, drove this growth, while agriculture, although increasing in absolute terms, saw a relative decline in contribution to regional income. Per capita income rose notably, reflecting concentrated development in resource-rich areas. National planning initiatives, including the Second and Fourth Five-Year Plans, fueled investments in heavy industries, minerals, and infrastructure. However, the region faces stark economic disparities, underdeveloped backward districts, limited tertiary sector engagement, and inadequate rural infrastructure. The report emphasizes the need for integrated development strategies that balance industrial expansion with agricultural enhancement, employment generation, and infrastructure development to ensure equitable and sustainable growth across all districts in the region.
Union Economic Development Including Demographic Aspects
Keywords: South East Resource Region; Industrial Development; Agriculture; Manufacturing Sector; Income Growth; Infrastructure; Regional Disparities; Employment Generation; Economic Planning; Sustainable Growth